2019
DOI: 10.1002/jcla.22919
|View full text |Cite
|
Sign up to set email alerts
|

Association between the rs2288947 polymorphism of the lncRNA TINCR gene and the risk of recurrent miscarriage in a Southern Chinese population

Abstract: Studies have shown that many genes that regulate cell migration are associated with susceptibility to recurrent miscarriage. Terminal differentiation‐induced non‐coding RNA (TINCR) regulates the migration and invasion of a variety of tumor cells and is associated with susceptibility to various diseases. However, whether the lncRNA TINCR polymorphism is associated with susceptibility to recurrent miscarriage is unclear. Therefore, we investigated the relationship between the rs2288947 A > G polymorphism of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…29 , 30 , 31 We had also carry on a study about relationship between LncRNA TINCR (rs2288947) polymorphisms and susceptibility of RM, but the result showed there was no significant correlation between rs2288947 and RM. 32 Positive result had arisen in our following researches, which indicated that some LncRNA polymorphisms related to breast cancer were also associated with the development of RM. Thus, there is reason to believe that more LncRNAs polymorphisms which might be association with RM are waiting to be found.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…29 , 30 , 31 We had also carry on a study about relationship between LncRNA TINCR (rs2288947) polymorphisms and susceptibility of RM, but the result showed there was no significant correlation between rs2288947 and RM. 32 Positive result had arisen in our following researches, which indicated that some LncRNA polymorphisms related to breast cancer were also associated with the development of RM. Thus, there is reason to believe that more LncRNAs polymorphisms which might be association with RM are waiting to be found.…”
Section: Discussionmentioning
confidence: 90%
“…Although the function of most LncRNAs is still unclear, many studies have revealed that some LncRNAs involve in the onset and development of abortion 29‐31 . We had also carry on a study about relationship between LncRNA TINCR (rs2288947) polymorphisms and susceptibility of RM, but the result showed there was no significant correlation between rs2288947 and RM 32 . Positive result had arisen in our following researches, which indicated that some LncRNA polymorphisms related to breast cancer were also associated with the development of RM.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNAs have received much attention in recent years due to their regulatory roles 43 . Some lncRNAs, such as TINCR, 31 CCAT2, 16 MALAT1, 44 and SOX2OT, 45 have already been involved in RSA pathogenesis. HOTAIR is associated with many human diseases, including breast cancer, 46 esophageal squamous cell carcinoma, 47 thyroid cancer, 48 cervical cancer, 49 chronic myeloid leukemia, 50 and polycystic ovarian syndrome 51 .…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28][29] Evidence showed that genetics might play different roles in susceptibility to RSA. 16 Few studies have reported an association between SNPs in lncRNA genes and RSA 30,31 ; however, no study has investigated the relationship of HOTAIR gene polymorphisms to RSA development. In the current study, we aimed to genotype HOTAIR rs12826786 C/T, rs920778 T/C, rs4759314 A/G, and rs1899663 G/T SNPs in order to explore such association in Iranian women.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs have been revealed to play important roles in various cellular functions, including affecting the pluripotency and differentiation of embryonic stem cells, regulating cell apoptosis and cell cycle, and performing important functions in the origin, growth, evolution, selection and other aspects of human life (9)(10)(11). Recent several researches have found that lncRNAs may be related to RSA (12,13). However, there is only one study investigating relation of lncRNA with unexplained recurrent pregnancy loss (URPL) (14).…”
Section: Introductionmentioning
confidence: 99%